Effect of a stylet on specimen sampling in thyroid fine needle aspiration: A randomized, controlled, non-inferiority trial - Luo, Pengfei; Mu, Xiali; Ma, Wei; Jiao, Dahai; Zhang, Peixin (Frontiers in Endocrinology, 2023)
Background: There is a cost advantage in using a needle without stylet over a needle with stylet in thyroid fine needle aspiration (FNA). This study aimed to elucidate the non-inferiority of thyroid FNA without a stylet (S-) to thyroid FNA with a stylet (S+) on specimen sampling. Methods: In this study, patients with thyroid nodules undergoing FNA were consecutively enrolled between May 2022 and July 2022. One experienced operator performed two punctures of each nodule with a stylet and without a stylet. Specimen adequacy was the primary outcome. Wald test was used for statistical analysis of the primary outcome. The difference in specimen adequacy between the two methods was expressed as a two-sided 95% confidence interval (CI). The S- method was considered non-inferior to the S+ method if the lower bound of the 95% CI of the S- minus S+ adequacy difference was greater than a predetermined non-inferiority margin of -10%. Results: A total of 149 patients (195 nodules) were enrolled in the study. A total of 167 of 195 nodules (85.64%) and 169 of 195 nodules (86.67%) were obtained adequate specimens using the S+ and S- methods, respectively. The difference in specimen adequacy (S- minus S+) between the two methods was 1.03% (95% CI, -5.83% to 7.88%). The lower bound 95% CI of the difference in specimen adequacy (-5.83%) was greater than the predetermined non-inferiority margin of -10%. The difference in the yield for malignancy was not significantly different between the two methods. Conclusion: Thyroid FNA without a stylet is non-inferior to thyroid FNA with a stylet on specimen sampling.